2016
DOI: 10.1146/annurev-linguistics-030514-124824
|View full text |Cite
|
Sign up to set email alerts
|

Language and Speech in Autism

Abstract: Autism is a developmental disability characterized by atypical social interaction, interests or body movements, and communication. Our review examines the empirical status of three communication phenomena believed to be unique to autism: pronoun reversal (using the pronoun you when the pronoun I is intended, and vice versa), echolalia (repeating what someone has said), and a reduced or even reversed production-comprehension lag (a reduction or reversal of the wellestablished finding that speakers produce less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 58 publications
(72 reference statements)
1
36
0
4
Order By: Relevance
“…Furthermore, autism spectrum disorder (ASD) and schizophrenia both have communication-related phenotypes. [86,87] Both have previously been linked to imprinting [88] and more recent empirical work strengthens this association. [89,90] Of particular interest for language is the LRRC16A gene, in which risk variants are maternally overtransmitted in cases of ASD.…”
Section: Mathematical Models Of Language Investmentmentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, autism spectrum disorder (ASD) and schizophrenia both have communication-related phenotypes. [86,87] Both have previously been linked to imprinting [88] and more recent empirical work strengthens this association. [89,90] Of particular interest for language is the LRRC16A gene, in which risk variants are maternally overtransmitted in cases of ASD.…”
Section: Mathematical Models Of Language Investmentmentioning
confidence: 66%
“…In addition, mouse models of Angelman syndrome also demonstrate altered ultrasonic vocalizations, indicating that there is nothing mechanical preventing something similar occurring in humans. Furthermore, autism spectrum disorder (ASD) and schizophrenia both have communication‐related phenotypes . Both have previously been linked to imprinting and more recent empirical work strengthens this association .…”
Section: Inferring Selfishness Versus Altruism From Imprinted Genesmentioning
confidence: 99%
“…ICD-11 face diferențiere între "tulburarea de spectru autist fără deficiență mintală și cu limbaj funcțional sau ușor afectat -6.A02.0", "tulburarea de spectru autist cu deficiență mintală și cu limbaj non-existent sau nefuncțional -6A02.1", tulburarea de spectru autist fără deficiență mintală, dar cu limbaj funcțional deficitar-6A02.2", tulburarea de spectru autist cu deficiență mintală și cu limbaj funcțional deficitar -6A02.3" tulburarea de spectru autist fără deficiență mintală, dar cu absența limbajului funcțional -6A02.4., tulburarea de spectru autist cu deficiență mintală și cu absența limbajului funcțional -6A02. (Gernsbacher, Morson, & Grace, 2016). Încă din 1988, cercetători care s-au implicat în studierea autismului (Rutter et al, 1988) aduceau dovezi observaționale asupra particularităților de limbaj din autism, putându-se aminti: (1)limbajul vorbit apare cu întârziere sau lipsește definitiv -fără a fi compensat de gesturi și mimică, (2) eșecul comunicării cu ceilalți, (3) eșec relativ în a iniția sau întreține o conversație, (4)limbaj stereotip și repetitiv, (5) folosirea pronumelui "tu" în loc de "eu", (7) Idiosincrazie (8) anormalități la nivelul prozodiei (înălțimea vocii, tensiunea vocii, rata, ritmul, intonația vorbirii).…”
Section: Fig 1 Relaunclassified
“…Although language development plays a key role in social development and may affect how ASD symptoms manifest, language impairments or social communication skill problems alone are not core ASD symptoms [17]. Gerbsbacher et al [18] reported that delayed language development is a common but not a universal characteristic of autism since some studies that measured language ability did not show that language development among individuals with ASD differed from typical language development.…”
Section: Introductionmentioning
confidence: 99%